Microstructure and compression deformation behavior in the quasicrystalreinforced Mg-8Zn-1Y alloy solidified under super-high pressure - 董允 林小娉 徐瑞 郑润国 樊志斌 刘士俊 王哲 (中国稀土学报：英文版, 2014)
The microstructure of Mg-8Zn-1Y alloy solidified under super-high pressure was analyzed through X-ray diffraction（XRD）, scanning electron microscopy（SEM） and energy dispersive spectroscopy（EDS）. And, compression deformation behavior at room-temperature was studied. The results showed that the microstructure of Mg-8Zn-1Y alloy solidified under ambient pressure and super-high pressure was both mainly composed of ■-Mg and quasicrystal I-Mg3Zn6 Y. Solidification under super-high pressure contributed to refining solidified microstructure and changing morphology of the intergranular second phase. The morphology of intergranular second phase（quasicrystal I-Mg3Zn6Y） was transformed from continuous network（ambient pressure） to long island（high pressure） and finally to granular（super-high pressure） with the increase in pressure. The compressive strength, yield strength and rupture strain of the samples solidified under ambient pressure were significantly improved from 262.6 MPa, 244.4 MPa and 13.3% to 437.3 MPa, 368.9 MPa and 24.7% under the pressure of 6 GPa, respectively. Under ambient pressure, cleavage plane on compressive fracture was large and smooth. When it was solidified under the pressure ranging from 4 to 6 GPa, cleavage plane on compressive fracture was small and coarse. In addition, dimple, tear ridge and lobate patterns existed.